In Vivo Genotoxicity Assessment of Gold Nanoparticles of Different Doses by Comet Assays (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gold nanoparticles were synthesis by green method using the soaked orange peels (citrus Sinensis) asreducing and stabilizing agent. The gold nanoparticles were diagnosed using the approved method, includingthe transmission electron microscope and the visible UV spectroscopy. Thus, the results of the diagnosisshowed the formation of spherical particles with a size of 36 nanometers. Their biological effects on the bonemarrow cells of albino mice were studied.Male albino mice were used in this study and randomly divided into seven groups. The first group wasthe control group injected with the physiological solution (Normal Saline) and the other six groups wereinjected with different doses of the solution of the gold nanoparticles (1, 2, 4, 6, 8 and 10) Mg/kg. The effectof gold nanoparticles on the DNA damage by bone marrow cells was studied using comet assay accordingto the following criteria:(DNA in Head%, Comet Length, Tail Length, DNA in Tail%, Olive Moment), the results showed a significantdecrease (P?0.01) in the rate of DNA in Head%, while it showed a significant increase in Comet Length,Tail Length, DNA in Tail%, Olive Moment compared to the control group and all Doses studied. The effectof gold nanoparticles was directly proportional to the increase in the studied doses. The dose was 10 mg/kg,which was the highest toxicity, followed by the dose of 8 mg/kg, then the rest of the doses was descending.